1990
DOI: 10.1002/pssb.2221590120
|View full text |Cite
|
Sign up to set email alerts
|

Optical Nonlinearities of GaAs‐Based Epitaxial Structures for All‐Optical Switching

Abstract: An experimental study is made of GaAs/AlGaAs monolithic bistable etalons fabricated by metalorganic vapor-phase epitaxy. Optical bistability is observed in the reflective mode, with a minimum threshold power of less than 3 mW and a switching contrast as high as 30: 1, with a cavity resonator designed to achieve simultaneously a high finesse and a high reflectivity contrast. The dispersive optical nonlinearity of the multiple quantum well active medium is measured as a function of the intracavity intensity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However where the carrier density dependence of the absorption a and the carrier lifetime z are written explicitly, and h u~ is the photon energy. The only possibility for the solution of (4) to display an asymptotic behavior like the right-hand side of (3) is that either s ( N ) or a ( N ) vanishes for a finite value of N . Although T is known to decrease with N due to bimolecular or Auger recombination, it does not vanish at a finite value of N .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However where the carrier density dependence of the absorption a and the carrier lifetime z are written explicitly, and h u~ is the photon energy. The only possibility for the solution of (4) to display an asymptotic behavior like the right-hand side of (3) is that either s ( N ) or a ( N ) vanishes for a finite value of N . Although T is known to decrease with N due to bimolecular or Auger recombination, it does not vanish at a finite value of N .…”
mentioning
confidence: 98%
“…These attractive properties are obtained using the large excitonic-resonant nonlinear refractive index Sn,, of GaAs MQWs at room temperature [3], which involves the photoexcitation of electron-hole pairs, initially created in the low-energy tail of the excitonic and band-to-band optical transitions (Urbach's tail), and subsequently thermalized in higherenergy states through interaction with the lattice vibrations. In the course of our studies of such bistable microcavities, it was found that, due to the short nonlinear medium length (typically 100 QWs with a 20 nm periodicity), optical bistability could only be observed in the highest finesse cavities [4], which suggested that the available nonlinear phase shift was limited by some saturation mechanism.In the nonsaturating regime, Sn,, is simply proportional to the intensity I , and it is well known that n, defined as &,,(I) = n,l is proportional to the linear absorption coefficient a0 [5]. It is thus possible to define a figure of merit nJao which gives information about the nonlinear efficiency of the material.…”
mentioning
confidence: 98%